Evaluation of toxicity, antioxidant, antidiarrheal activity and phytochemical Screening of methanolic extract of leaf and stem of actephila excelsa - Ani, Tahsina (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.